(3QSGdI aj daX CTjGAs - (3GdCUagGfj , CMeO Hf GdMSjf Hf CMeO, TgGH GdOjf CHh TLGY,J (B593 (3g` s
(3ChdgG (B:s
(3CYde Cf ai daX CpTjGA KdGKI ePGgH , GdChd s
(3BNQgG (B:s
(3Cf jdRege GdbdH hgh cKjQ hGddg CYde s
(3YdjgG Jedcs
(3hgj fHPI eGNhPI ef TQM GdTGajI dTjN GdESdGe RcQjG ef MGTjI GdYdGeI GdTfhfi ajeG jJYdb HdaX pCTjGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B199s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(196) s
Keywords: (3GdUQas